MINICOLECISTECTOMIA. LOS PRIMEROS 90 CASOS - Agulrre B., Renato (2024)
Along with the appearance of endoscopic cholecystectomy, the standards for the postoperative course of cholecystectomy have been drastically redefined, although similar results have been published in the pastas a result of more traditional surgical techniques. It seems that short hospital stay and fast return to work are more dependent on the protocol for management of the postoperative period rather titan the surgical technique. The true tecbnique of mini-cholecystectomy requires a complete redefinition of tbe operative technique and produces similar aesthetic and functional results as those of tbe endoscopic technique. For severa( years the author used small laparotomiesf or selected cholecystectomy cases, maintaining the traditional technical maneuvers for the extirpation ofthe gallbladder. Tbis experience evolved into drastic changes to the tecnique of cholecystectomy, a quite different procedure tbat we call mini-cbolecystectomy, and eventually allowed to offer tbls proced ureas the preferred method f or extirpation of the gallbladder when there is no obstruction of the common ducL 90 consecutive and non-selected cases are presented, demonstrating that the results of the endoscopic technique are not exclusive. Based on the author's experience with mini-laparotomy for cholecystectomy and mini-cholecystectomy and data from the.literature, an attempt to establish a role for this tecnique is expressed.